2012
DOI: 10.1111/j.1748-720x.2012.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Companies and Global Lack of Access to Medicines: Strengthening Accountability under the Right to Health

Abstract: Many medicines currently available on the market are simply too expensive for millions around the world to afford. Many medicines available in the developing world are only available to a small percentage of the population due to economic inequities. The profit-seeking behavior of pharmaceutical companies exacerbates this problem. In most cases, the price reductions required to make drugs affordable to a broader class of people in the developing world are not offset by the resultant increase in sales volume. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 13 publications
(6 reference statements)
0
13
0
3
Order By: Relevance
“…Health research is claimed to drive inequality in access to medicine in two ways [ 78 , 79 ]. Firstly, by the pharmaceutical industry allocating only very limited resources to research into medicine for diseases primarily found among the poor.…”
Section: Discussionmentioning
confidence: 99%
“…Health research is claimed to drive inequality in access to medicine in two ways [ 78 , 79 ]. Firstly, by the pharmaceutical industry allocating only very limited resources to research into medicine for diseases primarily found among the poor.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while medical ethics and business ethics are distinct, the regulation of pharmaceutical companies and intellectual property rights certainly has bearing on access to medicines (cf. Grover et al 2012). Now, the important point here is not about any particular such issue, but simply to make clear that in order to develop reasonable approaches to problems located in such overlaps between domains does not presuppose that we should move up to a higher level of abstraction and then derive a solution from there, which would presumably be our main method of resolving conflicts if we were primarily oriented towards vertical integration and traditional moral theorizing.…”
Section: From Vertical To Horizontal Integrationmentioning
confidence: 99%
“…343-377 avatares, el resultado final de estas movilizaciones fue la Declaración de Doha sobre los ADIPC y la Salud Pública adoptada en 2001, que establece que los TRIPS podían y debían interpretarse y aplicarse de tal forma que permitiesen a los Estados proteger la salud pública y promover el acceso a los medicamentos para todas las personas. Esta declaración «ha sido esencial para hacer que las versiones genéricas de bajo coste de medicamentos patentados estén disponibles a gran escala» (Hoen et al, 2011) y con ello se cambió el rumbo del VIH en los países de renta baja (Kumarasamy et al, 2003) porque cuando los productores de medicamentos genéricos entran en el mercado los precios de todos los medicamentos bajan drásticamente (Grover et al, 2012).…”
Section: El Acceso a Los Medicamentos Esenciales Para Tratar O Prunclassified